Personalized Medicine: Harnessing an Artificial Intelligence Platform to Dynamically Individualize Combination Therapy for Treating Colorectal Carcinoma in a Rat Model (Adv. Therap. 4/2020). Issue 4 (17th April 2020) - Ding, Xianting; Chang, Vincent H. S.; Li, Yulong; Li, Xin; Xu, Hongquan; Ho, Chih‐Ming; Ho, Dean; Yen, Yun
Abstract : In article number 1900127, Chih‐Ming Ho, Dean Ho, Yun Yen and co‐workers harness an artificial intelligence platform that is mechanism free and can dynamically optimize combinatorial colorectal carcinoma therapy in rats. The individually optimized regimen reveals starkly different drug–dose parameters, which can converge each rat toward the same low tumor response rate.